Polyurethane pouring sealant with high thermal conductivity and preparation method thereof

By using specific combinations of thermal conductivity fillers and controlling particle size in polyurethane potting, the problem of insufficient thermal conductivity in the prior art is solved, and a polyurethane potting with high thermal conductivity and low viscosity is achieved, suitable for high-power electronics The heat dissipation problem of the device.

CN119242250AActive Publication Date: 2025-01-03SHANGHAI FUMING SEALING MATERIAL
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411632970.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-03
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing polyurethane potting glue has insufficient thermal conductivity in high-power electronic components and cannot effectively solve the heat dissipation problem.

Method used

A method for preparing a highly thermally conductive polyurethane potting adhesive using components A and B, wherein component A includes MDI, a first plasticizer and a first thermally conductive filler (composition of BN nanosheets, spherical alumina, diamond powder) Component B includes a polyol, a second plasticizer and a second thermally conductive filler. By controlling the particle size and proportion of the thermally conductive filler, the balance of thermally conductive effect and viscosity is ensured.

Benefits of technology

It realizes the high thermal conductivity and low viscosity of polyurethane potting, which is suitable for potting requirements, and effectively improves the heat dissipation performance and service life of electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of pouring sealants, in particular to a high-thermal-conductivity polyurethane pouring sealant and a preparation method thereof.The high-thermal-conductivity polyurethane pouring sealant is prepared from a component A and a component B, the component A is prepared from the following raw materials: MDI, a first plasticizer, a first heat-conducting filler and a first dispersing agent; the component B is prepared from the following raw materials: polyol, a second plasticizer, a second heat-conducting filler and an auxiliary agent; the first heat-conducting filler and the second heat-conducting filler are compositions comprising BN nanosheets, spherical aluminum oxide and diamond powder; the average particle size of the BN nanosheets is greater than that of the spherical aluminum oxide; the average particle size of the spherical aluminum oxide is 2-12 [mu] m; the spherical aluminum oxide at least comprises first spherical aluminum oxide and second spherical aluminum oxide; the average particle size of the first spherical aluminum oxide is larger than that of the second spherical aluminum oxide. The polyurethane pouring sealant prepared by the invention is low in viscosity, good in flowability and high in heat conductivity coefficient, and has higher practical value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of potting adhesives, and in particular to a high thermal conductive polyurethane potting adhesive and a preparation method thereof. Background Art

[0002] With the rapid development of the electronics industry, the application scenarios of potting glue are increasing, and the requirements for potting glue are getting higher and higher. As a typical representative of potting glue, the demand for polyurethane potting glue is also increasing year by year.

[0003] Chinese patent CN116656306B discloses a polyurethane potting glue, including A material component and B material component; the A material component includes castor oil, a first polyether polyol, a second polyether polyol, a mixing aid, and aluminum hydroxide; the B material component includes polymerized MDI; the mixing aid is a mixture of a wetting dispersant, a viscosity reducer, and a defoamer. The invention solves the problem that the defoaming ability of the potting glue on the market is not enough to completely eliminate bubbles, and even if the bubbles can be completely eliminated, an excessive amount of defoamer needs to be added to completely eliminate the bubbles.

[0004] However, the potting glue in the above-mentioned prior art cannot solve the heat dissipation problem of high-power electronic components well, and its thermal conductivity still needs to be improved. Summary of the invention

[0005] In order to solve the problems in the prior art, the first aspect of the present invention provides a high thermal conductive polyurethane potting adhesive, wherein the raw materials for preparing the polyurethane potting adhesive include: component A and component B; the raw materials for preparing the component A include MDI, a first plasticizer, a first thermal conductive filler, and a first dispersant; the raw materials for preparing the component B include polyol, a second plasticizer, a second thermal conductive filler, and an auxiliary agent; the first thermal conductive filler and the second thermal conductive filler are both a composition of BN nanosheets, spherical alumina, and diamond powder; The average particle size of the BN nanosheets is larger than the average particle size of the spherical alumina; the average particle size of the spherical alumina is 2-12 μm; the spherical alumina comprises at least a first spherical alumina and a second spherical alumina; the average particle size of the first spherical alumina is larger than the average particle size of the second spherical alumina.

[0006] In one embodiment, the average particle size of the BN nanosheets is 18±2 μm.

[0007] The applicant creatively discovered that when the average particle size of the BN nanosheets in the system is larger than the average particle size of the spherical alumina, especially when the average particle size of the BN nanosheets is 18 μm, the polyurethane potting adhesive finally prepared has good thermal conductivity and low viscosity. The possible reason is that when the average particle size of the BN nanosheets in the system is too large, the sedimentation performance of the product is reduced, and when the average particle size of the BN nanosheets in the system is too small, the viscosity of the product is high and the flowability is reduced.

[0008] In one embodiment, the average particle size of the first spherical aluminum oxide is 12 μm.

[0009] In one embodiment, the average particle size of the second spherical aluminum oxide is 2 μm.

[0010] In one embodiment, the average particle size of the diamond powder is 12 μm.

[0011] The applicant found that the selection of thermally conductive fillers has a great influence on the dispersion effect. When irregular alumina or flaky alumina is used, the final polyurethane potting glue has high viscosity and poor thermal conductivity. The applicant creatively found that when the thermally conductive filler includes spherical alumina of different particle sizes, especially when the particle size of the spherical alumina is controlled to be a combination of 2μm and 12μm, the final polyurethane potting glue can be guaranteed to have good stability, fluidity and thermal conductivity.

[0012] In one embodiment, the mass ratio of the first spherical alumina to the second spherical alumina is (20-46): (45-46).

[0013] In one embodiment, the mass ratio of the first spherical alumina to the second spherical alumina is 4:9.

[0014] In one embodiment, the mass ratio of the total mass of the first plasticizer and MDI to the mass of the first thermally conductive filler is 12:92.

[0015] In one embodiment, the mass ratio of the total mass of the polyol and the second plasticizer to the mass of the second thermally conductive filler is 8:91.

[0016] In one embodiment, the first plasticizer and the second plasticizer are both one or more of epoxidized soybean oil, DOA, DOTP, DOP, TCP, and TCPP.

[0017] In one embodiment, the first plasticizer is a combination of epoxidized soybean oil and DOA.

[0018] In one embodiment, the mass ratio of the epoxidized soybean oil to DOA is 1:3.

[0019] In one embodiment, the epoxidized soybean oil is purchased from Tongxiang Chemical.

[0020] In one embodiment, the second plasticizer is DOA, and the DOA is purchased from Kunshan Weifeng Chemical.

[0021] In one embodiment, the auxiliary agent includes one or more of a molecular sieve, a defoaming agent, a catalyst and a second dispersant.

[0022] In one embodiment, the auxiliary agent includes a molecular sieve, a defoaming agent, a catalyst and a second dispersant.

[0023] In one embodiment, the molecular sieve is 5A molecular sieve, and the 5A molecular sieve is purchased from Luoyang Jianlong Micro-Nano New Materials Co., Ltd.

[0024] In one embodiment, the defoaming agent is selected from any one of an organosilicon defoaming agent and a non-silicon defoaming agent.

[0025] In one embodiment, the defoamer is a non-silicon defoamer, and the brand of the non-silicon defoamer is BYK-2735, which is purchased from BYK Chemicals.

[0026] In one embodiment, the catalyst is selected from any one of an organic tin catalyst and a polyurethane delay catalyst.

[0027] In one embodiment, the catalyst is an organotin catalyst, the brand of the organotin catalyst is MT101, purchased from Mingtai Chemical.

[0028] In one embodiment, the first dispersant and the second dispersant are both BYK-9076, purchased from BYK Chemicals.

[0029] In one embodiment, the mass ratio of the mixture of the first plasticizer and the first thermally conductive filler to the first dispersant is 500:1.

[0030] In one embodiment, the mass ratio of the mixture of the polyol, the second plasticizer and the second thermally conductive filler to the second dispersant is 1000:3.

[0031] In one embodiment, the polyol includes one or more of castor oil, modified castor oil, modified soybean oil polyol, modified cashew nut shell oil polyol, polyether polyol, dipropylene glycol, 1,4-butanediol, ethylene glycol, and 2-ethyl-1,3-hexanediol.

[0032] In one embodiment, the polyol includes one or both of castor oil and dipropylene glycol.

[0033] In one embodiment, the polyols are castor oil and dipropylene glycol.

[0034] In one embodiment, the mass ratio of the second plasticizer to castor oil and dipropylene glycol is 2:9:1.

[0035] In one embodiment, the MDI includes any one of pure MDI, liquefied MDI, and polymeric MDI.

[0036] In one embodiment, the MDI is liquefied MDI with a brand name of MDI-100L, purchased from Wanhua Chemical.

[0037] A second aspect of the present invention provides a method for preparing a high thermal conductive polyurethane potting adhesive, characterized in that it comprises at least the following steps: S1. Preparation of component A: After the first plasticizer, the first thermal conductive filler and the first dispersant are completely dispersed, MDI is added, the mixture is mixed and discharged, and the mixture is sealed and stored to obtain component A; S2. Preparation of component B: uniformly mix the polyol, the second plasticizer, the second thermal conductive filler and the auxiliary agent, discharge the mixture, and seal and store the mixture to obtain component B.

[0038] In one embodiment, the preparation of component A includes the following steps: pre-dispersing the first plasticizer and BN nanosheets, and then entering the homogenizer to disperse for 30-60 minutes, adding spherical alumina, diamond powder and the first dispersant, dispersing for 30 minutes, heating to 110-130°C, turning on the vacuum equipment to remove water for 120 minutes, testing the moisture content of the material, and when the moisture content is lower than 150ppm, cooling to 60°C, adding MDI, mixing for 30 minutes, discharging, and sealing to obtain component A.

[0039] In one embodiment, the vacuum degree of the vacuum equipment is set to 0.1 MPa.

[0040] In one embodiment, the preparation of the B component includes the following steps: pre-dispersing the polyol, the second plasticizer and the BN nanosheets, and then entering the homogenizing equipment for dispersion for 30 to 60 minutes, adding spherical alumina, diamond powder and the second dispersant, and dispersing for 30 minutes, heating to 110-130°C and turning on the vacuum equipment to remove water for 120 minutes, testing the moisture content of the material, and when the moisture content is lower than 150ppm, cooling to 75-85°C, adding molecular sieves, defoaming agents and catalysts, mixing and dispersing for 30 minutes, and turning on the vacuum at the same time; after mixing evenly, discharging the material, sealing and storing, and obtaining the B component.

[0041] In one embodiment, the pre-dispersion time is 10 minutes.

[0042] Beneficial Effects 1. Based on the system of the present invention, spherical alumina with different particle sizes are used in combination, especially when the average particle size of the spherical alumina is controlled to be a combination of 2 μm and 12 μm and the mass ratio of the two spherical aluminas is controlled, it can be ensured that the finally prepared polyurethane potting glue has good stability, fluidity and thermal conductivity.

[0043] 2. Based on the system of the present invention, when the particle size of the BN nanosheets in the thermal conductive filler is controlled to be larger than the particle size of the spherical alumina, especially when the average particle size of the BN nanosheets is 16-18 μm, the polyurethane potting glue finally prepared has good thermal conductivity and low viscosity.

[0044] 3. The present invention can obtain a polyurethane potting adhesive with high thermal conductivity by selecting a specific combination of thermally conductive fillers and strictly controlling the usage ratio of each component in the thermally conductive filler and the usage of the thermally conductive filler.

[0045] 4. The polyurethane potting glue prepared by the present invention has low viscosity and good fluidity, which is suitable for potting requirements, and has a high thermal conductivity, which can better solve the heat dissipation problem of electronic components and improve the service life of client products.

[0046] 5. The preparation method of the polyurethane potting glue provided by the present invention can be applied to industrial production and has higher practical value. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The experimental methods in the examples without specifying specific conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.

[0048] Examples 1-4, Comparative Examples 1-4 Embodiments 1-4 and Comparative Examples 1-4 of the present invention provide a high thermal conductive polyurethane potting adhesive in the first aspect. The raw materials for preparation are shown in Table 1 and Table 2 respectively in parts by weight.

[0049] Embodiments 1-4 and Comparative Examples 1-4 of the present invention provide a second aspect of a method for preparing a high thermal conductive polyurethane potting adhesive, comprising the following steps: Preparation of component A: pre-disperse the first plasticizer and BN nanosheets for 10 minutes, then disperse them in a homogenizer for 40 minutes, add spherical alumina, diamond powder and the first dispersant, disperse for 30 minutes, heat to 120°C, start a vacuum device to remove water for 120 minutes, test the moisture content of the material, and when the moisture content is lower than 150ppm, cool to 60°C, add MDI, mix for 30 minutes, discharge the material, and seal it for storage to obtain component A.

[0050] The preparation of the B component comprises the following steps: pre-dispersing the polyol, the second plasticizer and the BN nanosheets for 10 minutes, then dispersing them in a homogenizing device for 40 minutes, adding spherical alumina, diamond powder and the second dispersant, dispersing them for 30 minutes, heating the temperature to 120° C., turning on a vacuum device to remove water for 120 minutes, testing the moisture content of the materials, and when the moisture content is lower than 150 ppm, cooling the temperature to 80° C., adding a molecular sieve, a defoaming agent and a catalyst, mixing and dispersing for 30 minutes, and turning on a vacuum at the same time; discharging the materials after mixing them evenly, and sealing and storing them to obtain the B component.

[0051] Performance Testing 1. Viscosity test: The components A and B prepared in Examples 1-4 and Comparative Examples 1-4 were subjected to viscosity tests using a rheometer (Netzsch, Lab+). The test results are shown in Tables 1 and 2.

[0052] 2. Thermal conductivity test: The samples prepared in Examples 1-4 and Comparative Examples 1-4 were respectively made into 2 mm thick sheets, and then cut into sizes of 20 mm*20 mm*2 mm, and tested using a thermal conductivity tester (Hot disk TPS3500). The test results are shown in Table 3, where / indicates that the relevant test could not be performed.

[0053] Thin sheet preparation method: Weigh component A and component B at a weight ratio of 104:100 with an electronic balance, stir evenly with a glass rod, and then put them into a vacuum dryer for vacuum degassing. When no obvious bubbles are generated on the surface of the glue, turn off the vacuum dryer, pour the glue into a 2mm thick mold and cure it at room temperature for 72 hours. The 2mm thick thin sheet is completed.

[0054] Table 1

[0055] Table 2

[0056] Table 3

Claims

1. A high thermal conductivity polyurethane potting adhesive, characterized in that: The raw materials for preparing the composite material include: component A and component B; the raw materials for preparing component A include MDI, a first plasticizer, a first thermally conductive filler, and a first dispersant; the raw materials for preparing component B include polyol, a second plasticizer, a second thermally conductive filler, and an auxiliary agent; the first thermally conductive filler and the second thermally conductive filler are both a composition including BN nanosheets, spherical alumina, and diamond powder; The average particle size of the BN nanosheets is larger than the average particle size of the spherical alumina; the average particle size of the spherical alumina is 2-12 μm; the spherical alumina comprises at least a first spherical alumina and a second spherical alumina; the average particle size of the first spherical alumina is larger than the average particle size of the second spherical alumina.

2. The high thermal conductivity polyurethane potting adhesive according to claim 1, characterized in that: The mass ratio of the first spherical alumina to the second spherical alumina is (20-46):(45-46).

3. The high thermal conductivity polyurethane potting adhesive according to claim 1, characterized in that: The first plasticizer and the second plasticizer are one or more of epoxidized soybean oil, DOA, DOTP, DOP, TCP, and TCPP.

4. The high thermal conductivity polyurethane potting adhesive according to claim 1, characterized in that: The auxiliary agent includes one or more of a molecular sieve, a defoaming agent, a catalyst and a second dispersant.

5. The high thermal conductivity polyurethane potting adhesive according to claim 1, characterized in that: The polyol includes one or more of castor oil, modified castor oil, modified soybean oil polyol, modified cashew nut shell oil polyol, polyether polyol, dipropylene glycol, 1,4-butanediol, ethylene glycol, and 2-ethyl-1,3-hexanediol.

6. A method for preparing the high thermal conductive polyurethane potting adhesive according to any one of claims 1 to 5, characterized in that: At least the following steps are included: S1. Preparation of component A: After the first plasticizer, the first thermal conductive filler and the first dispersant are completely dispersed, MDI is added, the mixture is mixed and discharged, and the mixture is sealed and stored to obtain component A; S2. Preparation of component B: uniformly mix the polyol, the second plasticizer, the second thermal conductive filler and the auxiliary agent, discharge the mixture, and seal and store the mixture to obtain component B.

Citation Information

Patent Citations

  • Low-viscosity high-thermal-conductivity two-component polyurethane adhesive and preparation method and application thereof

    CN111534268A

  • Heat-conducting pouring sealant as well as preparation method and use method thereof

    CN116496755A

  • Polyurethane composition with stable heat-conducting property as well as preparation method and application thereof

    CN118126283A

  • KR20240109620A